2016
DOI: 10.3389/fpsyg.2016.01543
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Rhythmic Preferences in the Budgerigar (Melopsittacus undulatus): A Comparative Study with Humans

Abstract: A variety of parrot species have recently gained attention as members of a small group of non-human animals that are capable of coordinating their movements in time with a rhythmic pulse. This capacity is highly developed in humans, who display unparalleled sensitivity to musical beats and appear to prefer rhythmically organized sounds in their music. Do parrots also exhibit a preference for rhythmic over arrhythmic sounds? Here, we presented humans and budgerigars (Melopsittacus undulatus) – a small parrot sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
0
19
1
1
Order By: Relevance
“…Figure 1 shows a diagram of the place preference chamber used to test humans. A large rectangular room was divided into two sides by a bisecting wall as described by Hoeschele and Bowling (2016). The left and right side were identical: they were lit by an overhead lighting fixture and contained a single speaker (M-Audio AV 40, Cumberland, RI, USA) placed at the end opposite the entrance to the chamber.…”
Section: Budgerigar Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows a diagram of the place preference chamber used to test humans. A large rectangular room was divided into two sides by a bisecting wall as described by Hoeschele and Bowling (2016). The left and right side were identical: they were lit by an overhead lighting fixture and contained a single speaker (M-Audio AV 40, Cumberland, RI, USA) placed at the end opposite the entrance to the chamber.…”
Section: Budgerigar Subjectsmentioning
confidence: 99%
“…The outer walls, ceiling, and floor of the chamber were the walls of the anechoic room, except for the entrance wall, which was made out of large cardboard sheets and heavy blankets. The bisecting wall was made out of heavy sheets of wood, cardboard, and blankets (Figure adapted from Hoeschele and Bowling 2016) room. This was done to reduce transmission of sound from one side of the chamber to the other.…”
Section: Budgerigar Subjectsmentioning
confidence: 99%
“…Individualised drumming styles, including variations in rhythm, suggest that information about the male may be conveyed to females (Heinsohn et al 2017). In budgerigars, Melopsittacus undulatus, experiments show that females prefer rhythmic sounds, which may relate to a preference for rhythm (as yet untested) in the head-bobbing sexual display given by males of the species (Hoeschele & Bowling 2016). In the current study, observed display calls were always given by adult males and directed towards their bonded females.…”
Section: Discussionmentioning
confidence: 99%
“…In males, right-sided dominance of molecular neuronal activation was found in answer to mate calls in the CMM male ( Eda-Fujiwara et al, 2016 ), several studies found that vocal learning in adult budgerigars is sex-biased ( Striedter et al, 2003 ). These differences in learning have been well documented at various developmental stages in males and females as well ( Hoeschele & Bowling, 2016 ). Nevertheless, the biological functions of gonadal miRNAs in budgerigars are largely unknown and the sexual differential expression (DE) profile of gonadal miRNAs in budgerigars has not been reported.…”
Section: Introductionmentioning
confidence: 91%